Pentalogy of Cantrell with thoracoabdominal ectopia cordis: Attempted surgical correction and review of recent literature to aid prognostication prior to surgery - Vered Lack; Christina Oetzmann von Sochaczewski; Krubin Naidoo; Jerome Loveland (Elsevier, 2015)
Complete ectopia cordis (EC) is a rare congenital condition where the heart is extrathoracic, uncovered by pericardium and skin. This condition is often accompanied by intracardiac as well as other congenital anomalies. The thoracoabdominal type is frequently associated with varying degrees of Pentalogy of Cantrell (POC). Unless addressed early post-natally, EC is incompatible with life. Surgery is usually staged, with cover of exposed organs an immediate priority, followed by repair of structural cardiac lesions. Formal repair of the chest wall is performed at a later stage. We present a case of thoracoabdominal EC with complete POC. The patient underwent surgery to cover the exposed heart and the abdominal wall defect, but demised within 48 h due to systemic sepsis. Data gained from a literature survey shows that if the congenital heart defect is haemodynamically stable, and if cover is achieved immediately after birth, there is an associated improved survival. In addition, antenatal diagnosis was found to improve planning of delivery, resulting in improved hemodynamic stability, decreased incidence of sepsis, shorter time to intervention and better overall survival.